New Muslims in the European Context : The Experience of Scandinavian Converts - Roald, Anne Sofie, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This volume deals with Scandinavian converts to Islam, discussing the process of conversion as well as the converts' role in Muslim communities and in majority society. As Islam is a new phenomenon in Scandinavia, the story of the new Muslims becomes also a story of the development of Scandinavian Islamic ideas. The book examines the specific features of Scandinavian society and Islamophobia in Scandinavia. It goes on to discuss the conversion process, Muslim convert trends common in Europe as well as in Scandinavia, and provides a detailed discussion of literature read or written by converts. The discussion of the new Muslims' experiences includes a discussion of the trend towards understanding Islam according to Scandinavian values.